Social determinants of human capital development in modern organization - S. O. Snisarenko (Омский научный вестник: Серия "Общество. История. Современность")
The article describes the social factors of the human capital formation and development in modern organizations. The content of the social policy of enterprises, the place of social protection of employees in the system of corporate social responsibility are analyzed. Modern principles and methods of social investment in human capital are proposed